2019
DOI: 10.1155/2019/9658267
|View full text |Cite
|
Sign up to set email alerts
|

Cerebroprotective Effect against Cerebral Ischemia of the Combined Extract ofOryza sativaandAnethum graveolensin Metabolic Syndrome Rats

Abstract: The novel strategy against ischemic stroke in metabolic syndrome (MetS) targeting at oxidative stress and inflammation has gained attention due to the limitation of the current therapy. Due to the antioxidant and anti-inflammation of the combined extract of Oryza sativa and Anethum graveolens, the cerebroprotective effect against cerebral ischemia in MetS condition has been focused. Since no data were available, this study was set up to determine the effects of the combined extract of Oryza sativa L. and Aneth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Our data have demonstrated that MetS rats with cerebral ischemia show the elevation of oxidative stress and inflammatory markers in the brain. These findings are corresponding with our previous study [11]. These changes give rise to brain damage which in turn induces the failure of ATPase pumps which resensitive to free radical reactions and lipid peroxidation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data have demonstrated that MetS rats with cerebral ischemia show the elevation of oxidative stress and inflammatory markers in the brain. These findings are corresponding with our previous study [11]. These changes give rise to brain damage which in turn induces the failure of ATPase pumps which resensitive to free radical reactions and lipid peroxidation.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, it has been demonstrated that the substance possessing antioxidant and anti-inflammation such as the combined extract of black stick rice and dill significantly improves brain damage and deficits in an animal model of ischemic stroke in MetS condition [10,11]. Our previous study also clearly demonstrates that the phytosome containing the combined extract of ginger rhizome and mulberry fruit (PMG) can also decrease oxidative stress and inflammation [12].…”
Section: Introductionmentioning
confidence: 84%
“…Multiple inflammatory-related cytokines are released in ischemic brain injury and participate in the damage and repair process of brain tissue, including ILs, TNF, interferon, and chemokines [ 45 , 46 ]. In addition, numerous data suggest that the inflammatory response is closely related to oxidative stress and aggravating I/R-induced cerebral injury [ 47 , 48 ]. Thus, it is clear that therapeutic drugs targeting the inflammatory response and oxidative stress can be very effective in improving cerebral I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of neuronal density in the sensorimotor cortex (bregma 1.6 to -3.0, anterior to posterior) was performed by using an Olympus light microscope type BH-2 (Japan) at 40x magnification. The analysis was performed specifically focused on neuropil, neuronal size, and shape [22]. The density of the survival neurons was expressed as the number of neurons per 255 μm 2 [22].…”
Section: Assessment Of Brain Infarctionmentioning
confidence: 99%